Anteseden Semangat Kerja Karyawan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This research was conducted with the aim of knowing the effect of communication, financial compensation, and non-physical work environment on morale. The location of this research is at PT. Unirama Kapal is located in Mengwi District, Badung Regency, Bali. This study involved all members of the population totaling 83 employees using a census technique. Data collection was carried out using a questionnaire which was measured using a Likert scale with five answer choices. Multiple linear regression analysis technique is used to answer the hypothesis. The results of the analysis prove that the magnitude of the influence of communication, financial compensation, and the work environment on morale is 88.9 percent. The dominant variable influencing morale is the non-physical work environment with a regression coefficient of 0.731. The results of the hypothesis test prove that communication, financial compensation, and the non-physical work environment have a positive and significant effect on morale.